Frontispiece and title page (Plate 5) from Description des expériences de la machine aérostatique de MM. de Montgolfier [Description of the aerostatic machine experiments of Mr. & Mr. Montgolfier] - Faujas-de-St.-Fond, cit. (Barthélemy) (Description des expériences de la machine aérostatique de MM. de Montgolfier, 1783)
Inscribed: "Expérience faite à Versaille, en présence de leurs Mejestés et de la Famille Royale, par Mr. Montgolfier, le 19 Sept. 1873. La Machine Aérostatique avoit 57 Pieds de haut sur 41 de Diamètre." On September 19, 1783, the Montgolfier brothers demonstrated their hot air balloon before King Louis XVI and the royal family at Versailles. A sheep, a rooster, and a duck were enclosed in a basket and tethered to the balloon in order to assess any risks of ascending to high altitudes. The balloon, which sustained two rips in its upper part, flew for around 8 minutes, reaching a height of around 500 m and travelling around 3 km before landing.
Keywords: Airships; Frontispiece; Ballooning; Title pages; Hot air balloons